Error Probability Exponents of Multiple Hypotheses Testing Illustrations - Grigoryan, Naira M. (Mathematical Problems of Computer Science, 2021)
The paper presents an application of multiple hypothesis testing for two Markov sources with virtual example in terms of text categorization problem. Some numerical experiments concerning Markov sources are considered. Our goal is to present numerical illustrations of interdependencies of error probability exponents as a supplementary to our previous theoretical paper [9].